STARD3 mediates endoplasmic reticulum‐to‐endosome cholesterol transport at membrane contact sites. (4th April 2017) - Wilhelm, Léa P; Wendling, Corinne; Védie, Benoît; Kobayashi, Toshihide; Chenard, Marie‐Pierre; Tomasetto, Catherine; Drin, Guillaume; Alpy, Fabien
Abstract: StAR‐related lipid transfer domain‐3 (STARD3) is a sterol‐binding protein that creates endoplasmic reticulum (ER)–endosome contact sites. How this protein, at the crossroad between sterol uptake and synthesis pathways, impacts the intracellular distribution of this lipid was ill‐defined. Here, by using in situ cholesterol labeling and quantification, we demonstrated that STARD3 induces cholesterol accumulation in endosomes at the expense of the plasma membrane. STARD3‐mediated cholesterol routing depends both on its lipid transfer activity and its ability to create ER–endosome contacts. Corroborating this, in vitro reconstitution assays indicated that STARD3 and its ER‐anchored partner, Vesicle‐associated membrane protein‐associated protein (VAP), assemble into a machine that allows a highly efficient transport of cholesterol within membrane contacts. Thus, STARD3 is a cholesterol transporter scaffolding ER–endosome contacts and modulating cellular cholesterol repartition by delivering cholesterol to endosomes. Synopsis: The cholesterol transfer protein STARD3, which scaffolds ER–endosome contact sites, controls cellular cholesterol distribution by efficiently delivering ER cholesterol to endosomes. STARD3 induces cholesterol accumulation in endosomes at the expense of the plasma membrane. STARD3‐mediated cholesterol routing depends on both its START domain‐dependent lipid transfer activity and its ability to create ER–endosome contacts with the ER‐anchored VAP proteins. In vitro reconstitution assays indicate that STARD3 and VAP assemble into a highly efficient cholesterol transport machine. Abstract : The cholesterol transfer protein STARD3, which scaffolds ER–endosome contact sites, controls cellular cholesterol distribution by efficiently delivering ER cholesterol to endosomes.